Tyrosine Kinase-2, Angiopoietin-2, and Thrombomodulin Axes in the Late-Onset Fetal Growth Restriction: A Prospective Cohort Study: - Altan Erbilen, Esra; Varol, Fusun Gulizar (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVE: Investigating the interaction among three interconnected proteins, namely receptor Tyrosine Kinase-2 (Tie-2), the vascular remodeling cytokine Angiopoietin-2 (Ang-2), and the coagulation inhibitor Thrombomodulin (TM), may offer fresh insights into the multifactorial origins of late-onset fetal growth restriction (LFGR). STUDY DESIGN: In this prospective cohort study, we assessed the maternal serum concentrations of Tie-2, Ang-2, and TM in pregnancies that developed LFGR (n=30) and a control group (n=59) within the gestational weeks of 32-39 gestational weeks at Trakya University Hospital (January 2021-December 2021). Concentrations were quantified using ELISA, and data analysis was conducted using the SPSS 22.0 Windows software package. RESULTS: The 75th percentile concentrations of these proteins were significantly lower in cases of LFGR. Among heavy smokers, the risk of LFGR increased by 2.37-fold. A significant correlation was observed between these proteins in both LFGR and healthy pregnancies. However, the sensitivity and specificity of these proteins within the Tie-2, Ang-2, and TM axes were 51%, 56%, 51%, and 45%, 52%, and 50%, respectively. When we examined cases where all three proteins exhibited a consistent trend, LFGRs accounted for 23.33% with reduced levels and 30% with elevated levels, whereas this pattern was observed in 40.67% with reduced levels and 42.37% with elevated levels in healthy pregnancies. CONCLUSION: Although our study underscores the significance of the intricate interactions between Tie-2, Ang-2, and TM proteins in LFGR pregnancies, it is evident that a more comprehensive investigation is required to make meaningful contributions to the clinical applicability of this subject.